Prevalence of reduced respiratory muscle strength in institutionalized elderly people - Simões, Rodrigo Polaquini; Castello, Viviane; Auad, Marco Antonio; Dionísio, Jadiane; Mazzonetto, Marisa (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVES: Respiratory muscle strength is relevant to the clinical situation of elderly patients, particularly those presenting with respiratory or cardiac diseases. The objectives of this study were to evaluate the respiratory muscle strength of institutionalized elderly women, compare this with predicted values for the Brazilian population and calculate the correlation with age and anthropometric characteristics. DESIGN AND SETTING: Cross-sectional study at the Department of Physiotherapy of Universidade Camilo Castelo Branco. METHODS: The participants were 56 institutionalized elderly women (74.87 ± 10.55 years of age), evaluated in eight institutions in three cities in the central region of the State of São Paulo, between January 2005 and March 2006. They were separated into three subgroups according to age: 60-69 years (n = 20), 70-79 (n = 18) and 80-89 years (n = 18). Maximal respiratory pressures were obtained using a manovacuometer. The values obtained were compared between subgroups and with predicted values. Correlation analysis was used to evaluate age, weight, height and body mass index in relation to maximal respiratory pressures. The significance level was P < 0.05. RESULTS: No significant differences in maximal respiratory pressures were seen between the three subgroups. The maximal respiratory pressures were significantly lower in the three subgroups, compared with predicted values. Negative correlations between maximal respiratory pressures and age and positive correlations in relation to weight, height and body mass index were found. CONCLUSIONS: Respiratory muscle strength was markedly reduced in institutionalized 60 to 89-year-old women and the values demonstrated correlations with age and anthropometric characteristics. CLINICAL TRIAL REGISTRATION NUMBER: ACTRN12608000136303